2009
DOI: 10.1519/jsc.0b013e3181bc1b7a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Swim Recovery and Muscle Stimulation on Lactate Removal After Sprint Swimming

Abstract: Competitive swimming requires multiple bouts of high-intensity exercise, leading to elevated blood lactate. Active exercise recovery has been shown to lower lactate faster than passive resting recovery but may not always be practical. An alternative treatment, electrical muscle stimulation, may have benefits similar to active recovery in lowering blood lactate but to date is unstudied. Therefore, this study compared submaximal swimming and electrical muscle stimulation in reducing blood lactate after sprint sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 24 publications
4
54
3
2
Order By: Relevance
“…An alternative treatment, ES, may have benefits similar to those of active recovery in lowering the blood lactate, but it has not yet been studied [14][15]18) . The lactic acid concentration in the blood was more significantly decreased in the ES group than in the static resting group in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An alternative treatment, ES, may have benefits similar to those of active recovery in lowering the blood lactate, but it has not yet been studied [14][15]18) . The lactic acid concentration in the blood was more significantly decreased in the ES group than in the static resting group in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Jang 17) reported that the lactate changed more significantly in the TENS group than in the resting group after anaerobic exercise. Neric et al 14) reported that after swimming-induced muscle fatigue, EMS (TENS) led to a lower mean blood lactate level (3.12 +/-1.41 mmol.L-1) after 20 min of recovery than with passive rest (4.11 +/-1.35 mmol.L-1). Blood lactate levels in submaximal swimming recovery were significantly poorer, however, at 10 min (3.506 +/-1.57 mmol.L-1) and 20 min (1.6060 +/-57 mmolL-1) after recovery without EMS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NMES involves a series of stimuli, delivered superficially using electrodes placed on the skin. It has been suggested that sub-tetanic NMES could be effective for enhancing sports recovery owing to its analgesic effects on muscle soreness [23], and its role on post exercise muscle metabolite removal, secondary to increased blood flow and lymphatic drainage to the stimulated area [24]. Low frequency electrical stimulation is the commonly used mode for the recovery process because it induces light muscle contraction responsible for muscle pump effect & therefore enhanced muscle blood flow.…”
Section: Introductionmentioning
confidence: 99%